Current practices in schooling transitions of students with developmental disabilities. (2017) - Rodriguez, Cathi Draper; Cumming, Therese M.; Strnadová, Iva
Highlights: Online survey of teachers was conducted to determine current transition practices. 167 teachers from three U.S. states completed the survey. Transition practices for students with developmental disabilities were identified. Implications for practice are presented. Abstract: This article examines the planning processes involved for students with developmental disabilities (i.e., intellectual disability and autism spectrum disorders) as they transition through different stages of schooling in the United States. In order to obtain an understanding of current practices in this area, 167 teachers from three states (California, Texas and North Carolina) were surveyed about transition practices for students with developmental disabilities. The transitions from primary to middle school, middle to high school, and high school to post-school life, as well as home-school collaboration, were the focus. The teachers responded to demographic and open-ended survey questions. Findings indicated that the lack of active student involvement in transition planning remains a serious concern across all three transitions.